Creation of an international registry to support discovery in schwannomatosis. Issue 2 (19th October 2016) - Ostrow, K. L.; Bergner, A. L.; Blakeley, J.; Evans, D. G.; Ferner, R.; Friedman, J. M.; Harris, G. J.; Jordan, J. T.; Korf, B.; Langmead, S.; Leschziner, G.; Mautner, V.; et al.
Abstract : Schwannomatosis is a tumor suppressor syndrome that causes multiple tumors along peripheral nerves. Formal diagnostic criteria were first published in 2005. Variability in clinical presentation and a relative lack of awareness of the syndrome have contributed to difficulty recognizing affected individuals and accurately describing the natural history of the disorder. Many critical questions such as the mutations underlying schwannomatosis, genotype‐phenotype correlations, inheritance patterns, pathologic diagnosis of schwannomatosis‐associated schwannomas, tumor burden in schwannomatosis, the incidence of malignancy, and the effectiveness of current, or new treatments remain unanswered. A well‐curated registry of schwannomatosis patients is needed to facilitate research in field. An international consortium of clinicians and scientists across multiple disciplines with expertise in schwannomatosis was established and charged with the task of designing and populating a schwannomatosis patient registry. The International Schwannomatosis Registry (ISR) was built around key data points that allow confirmation of the diagnosis and identification of potential research subjects to advance research to further the knowledge base for schwannomatosis. A registry with 389 participants enrolled to date has been established. Twenty‐three additional subjects are pending review. A formal process has been established for scientific investigators to propose research projects, identify eligible subjects, and seek collaborators from ISR sites. Research collaborations have been created using the information collected by the registry and are currently being conducted. The ISR is a platform from which multiple research endeavors can be launched, facilitating connections between affected individuals interested in participating in research and researchers actively investigating a variety of aspects of schwannomatosis. © 2016 Wiley Periodicals, Inc.